2010
DOI: 10.3109/0886022x.2010.486497
|View full text |Cite
|
Sign up to set email alerts
|

Improved plasma amino acids pattern following 12 months of supplemented low-protein diet in peritoneal dialysis patients

Abstract: Background: Decreased plasma essential amino acid (EAA) levels, increased nonessential amino acid (NEAA) levels, and low EAA to NEAA ratio (E/NEAA) are common in peritoneal dialysis (PD) patients and may impact uremic complications. In the present study, we investigate the impact of keto acids-supplemented lowprotein (sLP) diet on plasma amino acids (AAs) patterns in stable PD patients. Methods: This is a supplemental analysis of a previously published prospective and randomized trial. Thirty-nine PD patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Since the current PD guidelines recommend high-protein intake of no less than 1.2 g/kg ideal body weight (IBW)/day [13], very few clinical practice could answer this question. Based on what we have found in our recent published paper [14, 15], DPI of 0.6–0.8 g/kg/d resulted in neutral nitrogen balance, maintained good nutritional status, and improved plasma amino acids pattern in PD patients if together with keto acid during 12 months of followup. We, therefore, further assessed the effect of dietary intervention on peritoneal transport rate by analyzing PET results at baseline and 12th month in the original PD cohort.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Since the current PD guidelines recommend high-protein intake of no less than 1.2 g/kg ideal body weight (IBW)/day [13], very few clinical practice could answer this question. Based on what we have found in our recent published paper [14, 15], DPI of 0.6–0.8 g/kg/d resulted in neutral nitrogen balance, maintained good nutritional status, and improved plasma amino acids pattern in PD patients if together with keto acid during 12 months of followup. We, therefore, further assessed the effect of dietary intervention on peritoneal transport rate by analyzing PET results at baseline and 12th month in the original PD cohort.…”
Section: Introductionmentioning
confidence: 64%
“…The study population and methodology have been previously described in detail [14, 15]. Briefly, 60 PD patients with residual renal function (urine output ≥800 ml/d or eGFR ≥2 ml/min/1.73 m 2 ) who fitted the inclusion criteria were enrolled and randomized to low- (LP: DPI of 0.6–0.8 g/kg IBW/d), keto-acid-supplemented low- (sLP: DPI of 0.6–0.8 g/kg IBW/d with keto acids of 0.12 g/kg IBW/d, Ketosteril; Fresenius Kabi Co., Ltd., Beijing, China), or high- (HP: DPI of 1.0–1.2 g/kg IBW/d) protein group in the original study.…”
Section: Methodsmentioning
confidence: 99%
“…Keto acids are widely used in dialysis patients with end-stage renal disease [9,10]. The drug can effectively correct hypocalcemia, reduce blood PTH, elevate blood albumin and reduce blood phosphorus, so as to protect the patient's residual renal function.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of this, protein supplement appears to be a simple therapy that can be safely employed in protein energy wasting cases receiving CAPD, where it is tolerated [9]. Jiang et al reported that low protein diet combined with keto/amino acids significantly improved the pattern of plasma AAs in most patients receiving peritoneal dialysis [53]. In addition, a study by Boudville et al demonstrated that oral supplements, when taken before eating food, could improve caloric and protein intakes of PD patients significantly [54].…”
Section: Discussionmentioning
confidence: 99%